2022
DOI: 10.3390/life12071082
|View full text |Cite
|
Sign up to set email alerts
|

Boron Neutron Capture Therapy (BNCT) Mediated by Maleimide-Functionalized Closo-Dodecaborate Albumin Conjugates (MID:BSA) for Oral Cancer: Biodistribution Studies and In Vivo BNCT in the Hamster Cheek Pouch Oral Cancer Model

Abstract: Background: BNCT (Boron Neutron Capture Therapy) is a tumor-selective particle radiotherapy that combines preferential boron accumulation in tumors and neutron irradiation. Although p-boronophenylalanine (BPA) has been clinically used, new boron compounds are needed for the advancement of BNCT. Based on previous studies in colon tumor-bearing mice, in this study, we evaluated MID:BSA (maleimide-functionalized closo-dodecaborate conjugated to bovine serum albumin) biodistribution and MID:BSA/BNCT therapeutic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Also, some pharmacokinetic profiles have been reported for maleimide-carboranes. In this sense, some data for maleimide-functionalized closo-dodecaborate albumin conjugates indicate their biased distribution after intravenous administration to some cells as those neoplastic cells in oral cancer in hamster and glioma in rats, a maximal accumulation between 8 and 12 h after injection. Also, a low biodistribution is shared, but a sustained detection in some body samples (12–48 h) suggest slow metabolism compared to other known BNCT-agents as BPA; , similarly, longer effects and sustained detection were observed compared with BSH against murine colon cancer cells …”
Section: Pharmacokinetics Of Some Boron-containing Compoundsmentioning
confidence: 99%
“…Also, some pharmacokinetic profiles have been reported for maleimide-carboranes. In this sense, some data for maleimide-functionalized closo-dodecaborate albumin conjugates indicate their biased distribution after intravenous administration to some cells as those neoplastic cells in oral cancer in hamster and glioma in rats, a maximal accumulation between 8 and 12 h after injection. Also, a low biodistribution is shared, but a sustained detection in some body samples (12–48 h) suggest slow metabolism compared to other known BNCT-agents as BPA; , similarly, longer effects and sustained detection were observed compared with BSH against murine colon cancer cells …”
Section: Pharmacokinetics Of Some Boron-containing Compoundsmentioning
confidence: 99%
“…It offers advantages as low toxicity, amount of functional groups that are available for conjugation, biocompatibility. Some authors reported recently maleimide‐functionalized closo‐dodecaborate derivatives conjugated to HSA reached therapeutically useful boron concentration values in the malignant cells and T/N tissue ratios with no significant toxicity 93,94 . Interesting works of Popova et al where authors prepared fluorophore‐labeled homocystamide conjugates of HAS with multimodal functions (Figure 6).…”
Section: Debut Of the New Boron Agent Developed For Bnctmentioning
confidence: 99%
“…Control group: cancerized, not treated (data extracted from previous studies performed by our group [45] (n = 6 hamsters, 34 tumors).…”
Section: Gb-10/bnct Combined With Early Electroporation: In Vivo Bnct...mentioning
confidence: 99%
“…The absolute boron concentration values in tumor and precancerous tissues (the dose-limiting tissue) for the early EP + GB-10 group were 20.2 ± 9.6 ppm and 8.9 ± 1.1 ppm, respectively (tumor/precancerous tissue ratio = 2.3 ± 1.2). For the GB-10 group, the tumor and precancerous tissue absolute boron concentration values were 9.5 ± 2.4 ppm and 12.4 ± 1.4 Control group: cancerized, not treated (data extracted from previous studies performed by our group [45] (n = 6 hamsters, 34 tumors).…”
Section: Gb-10/bnct Combined With Early Electroporation: In Vivo Bnct...mentioning
confidence: 99%
See 1 more Smart Citation